Pengaruh Brand Ambassador Dan Testimoni Terhadap Minat Beli Online Shop Tokopedia Di Kota Malang - Andhinilarasati, Andhinilarasati; Hidayati, Nur; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to (1) To analyze the simultaneous influence of Brand Ambassador and Testimonials on Interest in Buying the Tokopedia Online Shop in Malang City, (2) To analyze the partial influence of Brand Ambassador on Interest in Buying the Tokopedia Online Shop in Malang City, (3) To analyze the partial influence Testimonial about interest in buying the Tokopedia online shop in Malang City. The population in this study were FEB students class 2022 - 2023. The number of samples or respondents taken based on the Hair et all formula was 55 students. Data collection in this research was carried out by distributing questionnaires via Google Form to each respondent. The results of this research show that there is an influence between the independent variables, namely Brand Ambassador and Testimonials, on the dependent variable, namely buying interest. Keywords: Brand Ambassador, Testimonials, Purchase Interest.